1999
DOI: 10.3354/dao037145
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo simulation model for assessing the risk of introduction of Gyrodactylus salaris to the Tana river, Norway

Abstract: ABSTRACT. The Tana river in northern Norway, the most productive salmon river in Europe, is free of Gyrodactylus salaris. Currently there is one salmon farm in operation on the Tana fjord. Because of the strong association between stocking of rivers with salmon and infestations with G. salaris there is national and international concern that the existing farm might lead to the introduction of the parasite to the Tana river. In response to these concerns a quantitative analysis of the nsk of introduction of G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…No specific salinity data, however, is available for the Sandeelva estuary, and values for this stage of the migration were derived from data for stations at the outlet of the Drammen watercourse estuary. Sensitivity analysis showed that salinity was the most influential variable for the final risk estimates; this is consistent with results of Paisley et al (1999) concerning the risk of transmission of G. salaris from farmed salmon to the Tana River, Norway. This emphasises the need for sufficient data on this variable to enable quantification of the risk.…”
Section: Discussionsupporting
confidence: 72%
“…No specific salinity data, however, is available for the Sandeelva estuary, and values for this stage of the migration were derived from data for stations at the outlet of the Drammen watercourse estuary. Sensitivity analysis showed that salinity was the most influential variable for the final risk estimates; this is consistent with results of Paisley et al (1999) concerning the risk of transmission of G. salaris from farmed salmon to the Tana River, Norway. This emphasises the need for sufficient data on this variable to enable quantification of the risk.…”
Section: Discussionsupporting
confidence: 72%
“…Control methods for outbreaks of classical swine fever (CSF) in the Netherlands have been evaluated by modelling (Jalvingh et al 1999, Klinkenberg et al 2003, and these techniques were used extensively to assess competing strategies for the control of foot-and-mouth disease (FMD) during and after the 2001 epidemic in the UK (Keeling et al 2001, Woolhouse et al 2001, Green & Medley 2002. Although historically limited to theoretical population studies (Levy & Wood 1992, des Clers 1993, the application of mathematical modelling to aquatic animal health has more recently been used to quantify the impact of bacterial kidney disease (BKD) on chinook salmon Oncorhynchus tschawytscha in North America (Hamel 2002), and a stochastic modelling approach was taken to quantitatively assess the risk of transferring Gyrodactylus salaris between specific locations (Paisley et al 1999, Høgåsen & Brun 2003. To our knowledge, this is the first detailed predictive study of the potential distribution of disease on a national scale by live fish movement.…”
mentioning
confidence: 99%
“…Those relevant to the introduction of aquatic pathogens include work by Paisley (2001) for the monogenetic trematode Gyrodactylus salaris that has negatively impacted populations of Atlantic salmon in Norway. For whirling disease, Bruneau (2001) reported a quantitative risk assessment for the introduction of M. cerebralis into Alberta, Canada, via the importation of live salmonids.…”
Section: Introductionmentioning
confidence: 99%